The Impact of Corporate Strategic Deviance on ESG Performance: Evidence from Chinese Listed Companies - Wang, Xiwei (International Journal of Global Economics and Management, 2024)
This study examines the relationship between corporate strategic deviance and environmental, social, and governance (ESG) performance using a sample of listed A-share companies in Shanghai and Shenzhen from 2010 to 2020. The findings reveal that companies with a higher degree of strategic deviance tend to exhibit poorer ESG performance. This result still holds after a series of robustness tests. Furthermore, the study conducts heterogeneity analysis and uncovers that non-state-owned companies, those with lower managerial capacity companies are more vulnerable to the negative effects of strategic deviance on ESG performance.